2018
DOI: 10.1111/cxo.12640
|View full text |Cite
|
Sign up to set email alerts
|

Automatic analysis of corneal nerves imaged using in vivo confocal microscopy

Abstract: Interest has grown over the past decade in using in vivo confocal microscopy to analyse the morphology of corneal nerves and their changes over time. Advances in computational modelling techniques have been applied to automate the estimation of sub-basal nerve structure. These objective methods have the potential to quantify nerve density (and length), tortuosity, variations in nerve thickness, as well as temporal changes in nerve fibres such as migration patterns. Different approaches to automated nerve analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 104 publications
(171 reference statements)
0
51
0
3
Order By: Relevance
“…The strength of deep learning is echoed by Oakley et al [44] who used corneal nerve segmentation in CCM images from macaques. Deep-learning-based approaches make the segmentation task relatively easier for the end user compared with the conventional approaches employing various filters and graphs [23]. In particular, compared with conventional machine-learning methods, such as support vector machines (SVM), deep learning reduces the need and additional complexity of feature selection and extraction, allowing the computer to learn features alongside the segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of deep learning is echoed by Oakley et al [44] who used corneal nerve segmentation in CCM images from macaques. Deep-learning-based approaches make the segmentation task relatively easier for the end user compared with the conventional approaches employing various filters and graphs [23]. In particular, compared with conventional machine-learning methods, such as support vector machines (SVM), deep learning reduces the need and additional complexity of feature selection and extraction, allowing the computer to learn features alongside the segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Markoulli [23] developed a nerve segmentation technique to delineate corneal nerve morphology in CCM. This involved processes ranging from filtering methods (with rapid implementation but low-contrast and imprecise focus) to more complex support vector machine approaches (which rely on features defined by the user).…”
Section: Introductionmentioning
confidence: 99%
“…Existing clinical research [1], [2] suggests that the morphological changes observable in numerous anatomical curvilinear structures -e.g., retinal blood vessels, coronary blood vessel, carotid or corneal nerve fibers -are closely related to the presence of many diseases. For example, several studies [1]- [6] have confirmed that some quantitative properties of the corneal nerves such as nerve fiber branching, density, length, and tortuosity are linked to eye and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal nerve damage and repair from surgical interventions may be reflected in nerve branching, while fungal keratitis patients usually exhibit lower nerve density [7]. Tortuosity is one of the most significant biomarkers reflecting variations in corneal nerve fibers, as larger tortuosity implies process of nerve degeneration and subsequent regeneration, leading to active neural growth [2]. In addition, ophthalmologists often use the tortuosity of corneal nerve fibers as an important clinical parameter to assess hypertensive retinopathy [8] and diabetic neuropathy [9]- [12], respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation